1996
DOI: 10.1002/(sici)1099-1352(199634/12)9:5/6<738::aid-jmr333>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antibody selection by phage display utilizing anti-phenobarbital antibodies

Abstract: The generation of new antibodies for diagnostic applications using phage display could greatly decrease the time and expense of new assay development but, to be effective, the process must yield antibodies with desired specificity and affinity comparable to those obtained by monoclonal antibody technology. In order to evaluate the ability of the phage selection process to yield antibodies with the desired specificity and affinity, a family of anti-phenobarbital antibodies were cloned as scFvs and Fabs and disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…It has been reported that scFvphage and Fab-phage have comparable display levels (Chapman et al, 1997), yet Fab-phage have been claimed to be superior for biopanning selection (Malone and Sullivan, 1996). Our study could not assess the impact of antibody format since the scFv-encoding phagemid, pSEX81, differs from the Fab-encoding phagemids by multiple sequence motifs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that scFvphage and Fab-phage have comparable display levels (Chapman et al, 1997), yet Fab-phage have been claimed to be superior for biopanning selection (Malone and Sullivan, 1996). Our study could not assess the impact of antibody format since the scFv-encoding phagemid, pSEX81, differs from the Fab-encoding phagemids by multiple sequence motifs.…”
Section: Discussionmentioning
confidence: 99%
“…18 We similarly constructed a control vector (parent scFv construct kindly provided by Dr. Mark A. Sullivan, University of Rochester), 19 which expresses an ER-targeted anti-phenobarbital-specific single-chain IB (pAAV-scFvphe KDEL IB ). Briefly, a phenobarbital-specific IB sequence with an in-frame ER targeting signal (KDEL) and c-myc epitope tag at the C terminus to facilitate immunocytochemical detection was cloned into the pBS-FBR mcs shuttle vector under the transcriptional control of the human cytomegalovirus promoter and a SV40-derived polyadenylation signal was included at the 3Ј end of the transcription unit.…”
Section: Construction Verification and Packaging Of Ib-expressing Rmentioning
confidence: 99%
“…scFv2-18, which recognizes cell surface mannans (data not shown) on blastoconidia and filamentous forms of Candida, and a control scFv, scFv5 (2), which recognizes a protein antigen expressed only on filamentous Candida, were prepared using the method of Kipriyanov et al (11). Because scFv does not contain an Fc region, but does contain the FLAG epitope tag (14), organisms were opsonized with a three-layer complex consisting of 10 g of scFv2-18 per ml, 10 g of M2 anti-FLAG mouse monoclonal antibody per ml (Sigma-Aldrich, St. Louis, Mo. ), and a 1:250 dilution of an immunoglobulin G (IgG) fraction of rabbit anti-mouse polyclonal antiserum (Jackson ImmunoResearch, West Grove, Pa.).…”
mentioning
confidence: 99%